The Temple in Jerusalem: Using the Sun to date its Origins - Reidinger, Erwin (Liber Annuus, 2011)
Abstract The evaluation of the Herodian Temple complex on the basis of building analysis allowed the position and orientation of the Solomonian Temple on the Holy Rock on the Temple Mount to be reconstructed. The examination of the orientation of the temple axis on the basis of astronomy led to the discovery that the Temple of Solomon was laid out on the axis of the rising sun on Pessach 957 BCE. It also proved possible to discover the day of consecration of the First Temple, the Day of the Holy Convocation, in 951 BCE. Together, these two dates produce the biblical construction period of seven years. The date of the consecration of the Second Temple was the Day of Atonement in the year 515 BCE. As these days are all movable feasts, they are valid only for the particular years given.